Using Soil Quality Index Plus to assess soil conditions and limiting factors for dryland farming - Latief Mahir Rachman (Universitas Sebelas Maret, 2020)
Agriculture 3.0 and Agriculture 4.0 requires appropriate agricultural practices, including soil data that are practical, accurate, and easy to understand. Using soil type maps and land suitability class maps for soil information not only challenges users but also does not provide soil quality information such as production potential and plant growth and production inhibitors. Other techniques that can provide more appropriate soil information for agricultural purposes are thus needed. This research suggests the soil assessment system Soil Quality Index Plus, which provides accessible information regarding soil conditions and plant growth and production inhibitors in the context of dryland farming. Field trials were conducted in 36 locations across five regencies in West Java, Indonesia. Soil Quality Index Plus accurately assessed soil quality by using 11 key parameters as a dataset: effective depth, texture class, bulk density, drainage, pH, cation exchange capacity, total organic nitrogen, available phosphate, exchangeable potassium, aluminum saturation, and total carbon organic. The majority of the soils studied were classified as medium soil quality, with low organic carbon being the most common limiting factor. Improved fertilizer management, especially the use of organic fertilizers, phosphate- and nitrogen-based fertilizers, and agricultural lime should be implemented in particular areas.